Pengembangan Kelompok Wanita Tani dalam Budidaya Tanaman Empon-Empon dan Sayuran Bersama Tanifoundation di Gondangrejo Karanganyar, Jawa Tengah: Development of Women Farmers' Group in Cultivating Empon-Empon and Vegetables with TaniFoundation in Gondangrejo Karanganyar, Central Java - Saloka, Gilang Aji; Setyaningrum, Annisa; Siwi, Christina Pralambang Tunggal; Widayati, Deandra Suci Nur; Ambarwati, Dina Putri; Aziz, Fahmi; Az Zahra, Fatimah; Yasin, Febri Nur; Hidayah, Fitria Nur; Kurniasari, Selamita Rusdiana; Antriyandarti, Ernoiz (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The Jesa Karya Women Farmers Group (KWT), located in Gondangrejo, Karanganyar, is one of the KWTs with developing vegetables and empon-empon growing commodities. There are many challenges faced by KWT Jesa Karya, both internally and externally, so support from various aspects is needed to encourage the development process of KWT Jesa Karya. Through an independent study program, this support is in farmer assistance carried out by TaniHub and agricultural students. The method used in this assistance is Participatory Rural Appraisal (PRA). Interviews and observations were also conducted to obtain information on farmer groups' empowerment and the problems investigated. Jesa Karya KWT is developed through socialization mentoring programs, assistance in vegetable cultivation to product marketing, discussions on strengthening farmer group institutions, monitoring, and evaluation. Mentoring shows changes in improving the quality of their agricultural products, developing post-harvest products, and digital marketing to strengthen the resilience of farmers in increasing their business scale, realizing self-reliance, and improving the welfare of members. Member participation in this activity can be seen from members' enthusiasm in every activity held in support and efforts to form an effective program for developing KWT Jesa Karya.